2012
DOI: 10.24198/pjd.vol24no1.15385
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the tooth whitening effect between strawberry juice and apple juice in-vitro

Abstract: Bleaching is the tooth whitening by applying chemical materials oxidizing the organic tooth pigmentation and creating smaller and lighter molecules. Commonly used in the tooth bleaching is hydrogen peroxide. Strawberry and apple contain hydrogen peroxide and ellagic acid which will bond with an unsaturated bond of the tooth pigmentation. The purpose of this research was to finding out and measuring the tooth whitening level and effectivity between the strawberry and apple juice. The type of this research was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
2
0
2
Order By: Relevance
“…Stephanie et al, demonstrated the teeth whitening effect of apple juice and strawberry juice in in-vitro studies, where strawberry juice was more effective in tooth whitening than apple juice [48,49].…”
Section: Resultsmentioning
confidence: 99%
“…Stephanie et al, demonstrated the teeth whitening effect of apple juice and strawberry juice in in-vitro studies, where strawberry juice was more effective in tooth whitening than apple juice [48,49].…”
Section: Resultsmentioning
confidence: 99%
“…Citric acid was incorporated in choline hydroxide to attain a neutral pH of the synthesized gel. It is attributed to possessing tooth bleaching action as well [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…23 Jus apel memiliki pH yang rendah karena mengandung berbagai jenis asam organik seperti asam askorbik, malik dan ellagik. 24 Jus apel kemasan yang digunakan dalam penelitian ini (Marigold, Malaysia) mengandung asam askorbik yang paling banyak dalam komposisinya. Larutan asam berdifusi kedalam rangkaian polimer dan memutuskan rantai polimer yang menyebabkan terjadinya ekspansi.…”
Section: Pembahasanunclassified